Hydrogen Evolution Reaction Highly Electrocatalyzed by Mwcnt/N-Octylpyridinum Hexafluorophosphate Metal-Free System - Aguirre-Quintana, M; Aguirre-Quintana, M (Elsevier Ltd, 2021)
A mixed electrocatalyst that consists of multi walled carbon nanotubes (MWCNTs) and the ionic liquid (IL) N-octylpyridinum hexafluorophosphate (OPyPF6) as binder (MWCNT/IL system) was used in the study of hydrogen evolution reaction. This electrocatalyst was compared to graphite/mineral oil (Gr), graphite/OPyPF6 (Gr/IL), MWCNT/mineral oil (MWCNT) systems. All systems were characterized by cyclic voltammetry determining that MWCNT/IL system is highly electrocatalytic (E onset = -0.3 V vs Ag/AgCl) in relation to the other systems studied containing MWCNT or IL separately. The presence of each of the components that form the electrodic surface is corroborated by XRD, Raman, and FESEM-EDX, and it is demonstrated by chronoamperometric analysis that MWCNT/IL system is highly stable. The efficiency of the electrode, determined by its electrocatalytic activity, is confirmed by the quantification by gas chromatography of the hydrogen produced. Moreover, an elevated TON value (16274) and faradaic efficiency close to 60% are calculated, in comparison to other electrocatalysts found in literature. All these attractive properties are complemented by the fact that the MWCNT/IL system is simple, novel and easy to prepare. © 2021